Level of antibiotic contamination in the major river systems: A review on South Asian countries perspective - Prabhjot Singh Jassal, Dapinder Kaur, Manpreet Kaur, Pallavi, Disha Sharma (Journal of Applied Pharmaceutical Science, 2023)
Antibiotics are medicines used to forestall and treat bacterial infections. They work by killing the bacteria or by making it difficult for them to develop and multiply. Various types of antibiotics were used worldwide. Due to their partial metabolization inside the body, the leftover antibiotics are discharged into rivers, seas, and oceans without pre-treatment. There are different sewage treatment plants available for antibiotics removal but these are not used efficiently. This review gives insight into the presence of different antibiotics in rivers of major south Asian countries. The area is thus chosen due to the increase in the annual consumption of antibiotics. The study includes five rivers of India named Kshipra, Musi, Ganga, Yamuna, and Gomti; two rivers of Sri Lanka named Kelani and Gin and one river each from Nepal and Bangladesh named Bagmati and Brahmaputra. The amount of antibiotics present varies from country to country and from river to river. The current review will therefore showcase the most prominent antibiotics found in these water sources.
Keywords: Antibiotics, pharmaceuticals, river water, contamination, treatment